Analysis of the Temporal and Spatial Properties of Platinum Plasma Using Pulsed Nd:YAG and CO2 lasers (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background:The impact of laser light and pulse duration on the hydrodynamic properties of plasma was studied in terms of electron temperature (Te), ion temperature (Ti), and ion rate (Z*).Materials and methods: The study was carried out in two stages: in the first phase, five energy levels of the Nd:YAG laser (1, 3, 5, 7, 9 J) and a pulse duration of (10 ns) were used at Full Width at Half Maximum (FWHM). In the second phase, five energy levels of the CO2 laser (1, 3, 5, 7, 9 J) with a (10 ns ) pulse duration .Results: It was observed that at energy values of (1, 3, 5, 7, 9) J for the Nd:YAG laser with a 10 ns  pulse duration, the electron temperature ranged from (214.79 to 690.97) eV. While the electron temperatures as a result of   Co2 laser is ranged between (84.93 to 414.99) eV.Conclusion: We observe the electron temperatures of platinum plasma produced as a result of the ND:YAG  laser  was produced with with the same  levels were higher than the electron temperatures of platinum plasma produced using a CO2 laser.